2013
DOI: 10.1111/mpp.12066
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cereal rust fungi by both class I and II defensins derived from the flowers of Nicotiana alata

Abstract: Defensins are a large family of small, cysteine-rich, basic proteins, produced by most plants and plant tissues. They have a primary function in defence against fungal disease, although other functions have been described. This study reports the isolation and characterization of a class I secreted defensin (NaD2) from the flowers of Nicotiana alata, and compares its antifungal activity with the class II defensin (NaD1) from N. alata flowers, which is stored in the vacuole. NaD2, like all other class I defensin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 52 publications
2
28
0
Order By: Relevance
“…Plant defensins are small, cysteine-rich proteins with antimicrobial activity. Floral defensins were first identified in Nicotiana alata and Petunia plants and are thought to have antifungal activity in vitro (62,63). The regulation of floral defensin remains unclear.…”
Section: Resultsmentioning
confidence: 99%
“…Plant defensins are small, cysteine-rich proteins with antimicrobial activity. Floral defensins were first identified in Nicotiana alata and Petunia plants and are thought to have antifungal activity in vitro (62,63). The regulation of floral defensin remains unclear.…”
Section: Resultsmentioning
confidence: 99%
“…Certain cationic plant defensins exhibit growth inhibitory activity against various fungi and oomycetes at micromolar (μM) concentrations and this potent antifungal activity translates into disease resistance against these pathogens in transgenic plants (Kaur et al 2011). In case of rust pathogens, it has been reported that Nicotiana alata defensins, NaD1 and NaD2, inhibit germination of urediniospores and mitigate germ tube growth and differentiation of Puccinia species, and confer resistance to crown rust in oat seedlings when applied as a foliar spray (Dracatos et al 2013). …”
Section: Introductionmentioning
confidence: 99%
“…The expression of radish defensin in trangenic wheat confers resistance to F. graminearum [54]. In addition, defensins isolated from the venom of the snake Bothrops jararaca [55], from the plant Nicotiana alata [56] and from mice [57] have been shown to be effective against some species of Fusarium. In our study, the IC50 against F. culmorum and F. graminearum of both Scapularisin-3 and Scapularisin-6 are considerably low (1 μM).…”
Section: Discussionmentioning
confidence: 99%